2011
DOI: 10.3402/ejpt.v2i0.7995
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of complicated grief

Abstract: Following the death of a loved one, a small group of grievers develop an abnormal grieving style, termed complicated or prolonged grief. In the effort to establish complicated grief as a disorder in DSM and ICD, several attempts have been made over the past two decades to establish symptom criteria for this form of grieving. Complicated grief is different from depression and PTSD yet often comorbid with other psychological disorders. Meta-analyses of grief interventions show small to medium effect sizes, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 32 publications
4
66
0
3
Order By: Relevance
“…Moreover, caregivers who performed the treatment showed a higher decrease of difficulty to identify emotions and confidence with closeness than caregivers who did not decide to perform it. This finding suggests the important role of a psychological treatment after bereavement in order to increase the ability to recognise own emotions and to focus own resources mainly on the self and less on the relationship with the others during the work of mourning (Angeletti et al, 2014;Lai et al, 2007;Reynolds et al, 1999;Rosner et al, 2011). Finally, the higher level of the prolonged grief risk (PG-12) score, assessed 1 month before the loss, was a good predictor of the onset of DSM V diagnosis of PCBD at 14 months after bereavement. It was interesting that this predictive association was significant only after inserting the variable treatment as covariate, suggesting the role of treatment in the successive onset of the PCBD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, caregivers who performed the treatment showed a higher decrease of difficulty to identify emotions and confidence with closeness than caregivers who did not decide to perform it. This finding suggests the important role of a psychological treatment after bereavement in order to increase the ability to recognise own emotions and to focus own resources mainly on the self and less on the relationship with the others during the work of mourning (Angeletti et al, 2014;Lai et al, 2007;Reynolds et al, 1999;Rosner et al, 2011). Finally, the higher level of the prolonged grief risk (PG-12) score, assessed 1 month before the loss, was a good predictor of the onset of DSM V diagnosis of PCBD at 14 months after bereavement. It was interesting that this predictive association was significant only after inserting the variable treatment as covariate, suggesting the role of treatment in the successive onset of the PCBD.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, there is increasing evidence that support the effectiveness of psychological treatments, such as supportive therapy (Piper et al, 2007), brief dynamic therapy (Angeletti et al, 2014;Lai et al, 2007;Marmar et al, 1988), meaning oriented therapy (Breitbart et al, 2004), cognitive therapy (Malkinson, 2007), attachment oriented psychotherapy (Wetherell, 2012), in dealing with the suffering of a loss (Reynolds et al, 1999;Shear et al, 2014) Many studies showed a positive correlation between insecure attachment style and symptoms of complicated grief (Fraley & Bonanno, 2004;Shear et al, 2007;van Doorn et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In a smaller study conducted at multiple sites, Boelen et al (63) reported similar findings, comparing Cognitive Behavioral Treatment (CBT) with supportive counseling for CG and found a significant reduction in CG symptoms and general psychopathology in the CBT group compared to supportive counseling. A number of small studies using a similar intervention have now been published, including Acierno et al (64), Asukai et al (65), Rosner et al (66), Papa et al (67) and Supiano and Luptak (68). Wagner et al (69) tested the effectiveness of an internet-based cognitive behavioral therapy for CG.…”
Section: Complicated Grief Treatmentmentioning
confidence: 99%
“…Mental health outcomes include depression, post‐traumatic stress disorder (PTSD), and difficulties in grieving that extend in duration and severity beyond the scope of “normal” grief symptoms, also termed complicated grief (CG) (Zisook et al, ). For the sake of clarity, it is useful to note that varying labels and definitions of CG have been proposed (e.g., prolonged grief disorder, persistent complex bereavement disorder; American Psychiatric Association, ; Maercker et al, ; Prigerson et al, ; Shear, ), with estimates of the prevalence and incidence of CG varying according to the definition and the population observed (for a brief review, see Rosner, Pfoh, & Kotoučová, ).…”
Section: Introductionmentioning
confidence: 99%